Microscopic analysis of copper current collectors and mechanisms of fragmentation under compressive forces. (September 2020) - Wang, H.; Leonard, D.N.; Meyer, H.M.; Watkins, T.R.; Kalnaus, S.; Simunovic, S.; Allu, S.; Turner, J.A.
Abstract: Extensive fragmentation of copper current collectors was observed after spherical indentation on prismatic and large-format pouch Li-ion cells by 3D X-ray computed tomography (XCT). Microscopic analysis including scanning electron microscopy (SEM), scanning transmission electron microscopy (STEM) and x-ray photoelectron microscopy (XPS) was carried out on copper current collectors from used commercial cells and pristine anodes. The copper-graphite cross-section images showed rough interface areas affected by reactions and diffusion in the used cell. Electron probe micro-analyzer (EPMA) element mapping showed the interface area was rich in oxygen and phosphorus. A detectable amount of phosphorus was also uniformly distributed inside the current collector. The same oxygen and phosphorus distributions were confirmed by STEM/EDS analysis. XPS depth profiles on multiple elements revealed the interface area of the aged anode was rich in Li, F, P, O and C and diffused at least 50 nm into the copper. In comparison, the pristine anode showed a very smooth C/Cu interface. No other elements were detected. For commercial cells, the reactions in the interface area and diffusion of multiple elements into the lattice and grain boundaries were responsible for the embrittlement of the copper current collectors. Permanent cell capacity loss was observed in electrochemical performance of the indented cells. Graphical abstract: Image 1 Highlights: Copper current collectors were studied using multiple microscopy techniques. Diffusion induced embrittlement was the main cause of fragmentation under pressure. The fragmented copper current collectors led to permanent cell capability loss.